Computation and Optimization of Structural Leaf Venation Patterns for Digital Fabrication. (March 2022) - Gokmen, Sabri
Abstract: The morphogenetic design process of networking patterns produces anisotropic structural systems that can offer generative solutions for custom design applications. As an example of this type of pattern application, the leaf venation algorithm is introduced that can be customized through parametric inputs and density maps. This method is extended onto mesh surfaces incorporating multiple software applications combining aspects of parametric design, optimization and digital fabrication. The dynamic workflow is presented using a case study project titled "Calyx, " a public artwork completed using the computational tools developed as part of the research. The networking structural pattern of the sculpture yielded to the development of a geometry optimization process that allowed the digital fabrication of planarized structural members. The technical aspects of the design development and post-rationalization process for the construction of leaf venations patterns are discussed. Highlights: Morphogenetic application of leaf venation produces anisotropic patterns for design applications. Simulation and agent-based generative of leaf venation algorithm is discussed. A computational geometry optimization protocol is for planar fabrication of a case study. A computer aided design workflow integrating various structural, geometric and fabrication parameters is discussed.